Effect of French maritime pine bark extract supplementation on metabolic status and serum vascular cell adhesion molecule-1 levels in patients with type 2 diabetes and microalbuminuria - Elham Navval-Esfahlan; Maryam Rafraf; Somayyeh Asghari; Hossein Imani; Mohammad Asghari-Jafarabadi; Sanaz Karimi-Avval (Elsevier, 2021)
Objectives: This study investigated the effect of French maritime pine bark extract (PBE) supplementation on metabolic parameters, vascular cell adhesion molecule 1 (VCAM-1), urinary albumin-to-creatinine ratio (UACR), and anthropometric indexes in patients with type 2 diabetes (T2DM) and microalbuminuria. Design: This randomized, double-blind, placebo-controlled clinical trial was conducted on 46 patients with T2DM and the evidence of microalbuminuria aged 30-65 years. Setting: Patients were recruited from the endocrinology clinic of Sina hospital (Tabriz, Iran) from March 2018 to April 2019. Interventions: The subjects were randomly assigned to receive two capsules/day each containing 50mg of PBE or placebo for eight weeks. Main outcome measures: Glycemic parameters, serum VCAM-1 and lipid profile, UACR, and anthropometric indexes were measured for all patients at baseline and the end of the study. Results: PBE supplementation significantly reduced glycosylated hemoglobin, VCAM-1, total cholesterol, UACR, waist circumference, and waist-to-height ratio compared to the placebo group at the end of the study (all P < 0.05). Changes in fasting blood glucose, insulin, triglyceride, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were not significant between the two groups (all P > 0.05). Conclusions: The study findings demonstrated some favorable effects of PBE supplementation on glycemic control, serum VCAM-1 and total cholesterol levels, and microalbuminuria, as well as abdominal obesity in patients with T2DM.